Pengaruh Opini Audit, Temuan Audit dan Tindak Lanjut Hasil Pemeriksaan terhadap Ketersediaan Laporan Keuangan di Situs Website Pemerintah - Febrina Sabrini; Vita Fitria Sari (Universitas Negeri Padang, 2024)
This research aims to examine the influence of audit opinions, audit findings, and follow-up to audit results on the availability of financial reports on local government websites. The sampling technique in this research was purposive sampling and this population was obtained from 542 regencies/cities throughout Indonesia in 2021 which were used as samples in this research. The type of data in this research is secondary data. The data analysis method used is logistic regression. The research results show that the variables audit opinion and audit findings have a positive effect on the availability of financial reports on local government websites. The follow-up variable on audit results has no effect on the availability of financial reports on local government websites.